AUTOMATIC TECHNIQUES FOR IDENTIFICATION OF MINUTIAE’S IN MORPHOLOGY STUDY OF TERRAIN - Mohan P Pradhan; M K Ghose (European Scientific Journal, ESJ, 2012)
Morphological aspect of a terrain hosts different categories and different types of patterns. These patterns are represented in different color code for visual interpretation. These patterns are referred to as minutiae's. These identified minutiae's play pivotal roles by assisting researchers in making qualitative assessment of the terrain during various purpose specific inferential studies related to it. This work aims at design and implementation of efficient and effective procedures that assists researchers in extracting minutiae's from a reference data. In this work the reference data taken into consideration is a skeletonized binary images hosting the minutiae’s.